Associations between music training and language fluency on cognitive control and processing speed - Bugos, Jennifer A.; Laubisch, Kya R.; Zhu, Angela; Avendaño, Jason Schmidt; Bryant, Judith B. (Frontiers in Psychology, 2026)
IntroductionScientific research has demonstrated that musical training and bilingualism contribute to enhanced executive functions (D’Souza et al., 2018). However, it is unknown whether fluency in three or more languages would confer additional cognitive benefits above bilingual and musician status. According to Patel’s OPERA Hypothesis, music shares many similar components of language and also contains a high level of task complexity and temporal elements (Patel, 2012). Previous studies suggest that music and language learning enhance executive functions in cognitive control mechanisms, improving the ability to inhibit irrelevant information, flexibly shift attention, and make quick decisions. This research sought to examine associations between bilingualism and language fluency in musicians as compared to multilingual non-musicians. Also, do adults who are fluent in three languages perform similarly to bilingual musicians? Our research assessed associations between multilingualism, cognitive performance, and musical training.MethodsFifty-five participants (19 bilingual musicians, 18 bilingual non-musicians, 18 multilingual non-musicians) completed measures of visual motor processing and cognitive control in the visual and auditory domains.ResultsResults of a two-way ANOVA revealed enhanced processing speed and cognitive control in visual and auditory domains for bilingual musicians as compared to bilingual and multilingual non-musicians.DiscussionOverall, multilingualism may not enhance executive functions beyond those acquired in music training.